FOCUS - SZTUKA CZY METODA? - Lisek-Michalska, Jolanta (Wydział Prawa i Administracji UAM, 2002)
There is a great diversity in the attitudes of academic sociologists and commercial researchers towards the focus method. They vary from ardent and enthusiastic support to scathing condemnation. This article is an attempt at juxtaposing the Author’s several years of experience in focus group study (both academic and commercial) with her methodological observations, backed up by extensive scientific literature on the subject. All aspects of focus research include problematic points that vary in the degree of significance for a comprehensive evaluation of the method. These doubts deal with the following suggested problem areas: the methodological status of focus group study, research procedure elements, processing the data obtained from the study, and the ethics of focus research. The Author also discusses the role of a session moderator, his personality and methods of work, as well as the methods of preliminary information collection from questionnaires, the reliability o f the data thus obtained, and the methods of selecting participants for a group study. Considerable space is devoted to defining the positive and negative group effects, among the negative effects stressing tendencies to: opinion standardisation in a group, opinion extremism, minority suppression, conformity, conflicting secondary aims, and others.
FOCUS - ART OR METHOD?